LOCATIONAL STUDY OF JUNIOR HIGH SCHOOL AND MADRASAH TSANAWIYAH USING GEOGRAPHY INFORMATION SYSTEM (GIS) AT CEPOGO SUBDISTRICT BOYOLALI DISTRICT IN 2016 - MS Khabibur Rahman; Jumadi Jumadi (Universitas Sebelas Maret (UNS), 2019)
This research was conducted to find out and analyze the coverage of junior high school and madrasah tsanawiyah services to the user community in Cepogo District. The research used descriptive geographical research method using map analysis and the data collection methods used were documentation studies and field observations. The data collection technique in this study used a population that includes all junior secondary schools and Islamic elementary schools in Cepogo sub-district with primary data in the form of school locations obtained through field measurements using GPS (Global Potential System) and secondary data obtained from agencies authority and results from previous studies. The data analysis technique used was secondary data analysis techniques and map analysis techniques using buffer analysis. The results showed that there was a difference between supply (number of elementary school graduates) and demand (study group) in which supply was greater than demand. In addition, the coverage of education facilities at the junior high school / MTs level in Cepogo District is in accordance with the minimum standards of the national education minister's regulation no. 24 of 2007 concerning the maximum distance to education facilities, which is no more than 6 km with no hazardous track.